Pengaruh atribut kualitas audit terhadap kepuasan klien (studi empiris pada Bank Perkreditan Rakyat di Pekanbaru) - Ruth A Pasaribu; Andreas '; Riska Natariasari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The purpose of this research is to find out the audit quality attributes, includes auditing experience, understand the client's industry, responsive to the needs of clients, adhering to common standards, the involvement of the leadership of CPA Firm, the involvement of audit committees, on client satisfaction. Data for this study was obtained from samples of all staff off accounting, manager of accounting, and internal auditor,whose working at BPR company in Pekanbaru. This research is using survey methods. Total respondents which is used in this research are 49% respondents (81.6%). The analyzing method is Double Regression methods using SPSS (Statistical Product and Service Solution) version 17. Result of the study indicates the auditing experience, understand the client's industry, responsive to the needs of clients, the involvement of the leadership of CPA Firm influence to client satisfaction. But adhering to common standards and involvement of audit committees have not and influence on client satisfaction. The coefficient of determination in this research were 78.3%, the four variables jointly influence dependent variable as much as 78.3%, while 21.7% is influenced by other unclear variables.Keywords: Attribute Audit Quality, Client Satisfaction.